Planes - Hall, Klay.; Balthazor-Flynn, Traci; Howard, Jeffrey M., 1969-; Lasseter, John.; Keach, Stacy; Kilmer, Val, 1959-; Edwards, Anthony, 1962-; Walt Disney Company; Walt Disney Studios Home Entertainment (Firm) (Los Angeles, CA : Walt Disney Studios Home Entertainment, 2013)
Dusty's a cropdusting plane with dreams of competing as a high-flying air racer. But he's not exactly built for racing, and he happens to be afraid of heights. So he turns to a seasoned naval aviator, who helps him qualify to take on the defending champ of the race circuit.
Keywords: Airplanes -- Drama; Airplane racing -- Drama; Aviones -- Teatro; Children's films; Animated films; Comedy films; Action and adventure films; Video recordings for the hearing impaired